Teores de metais pesados no solo e em mamoneira adubada com lodo de esgoto - Kênia Máximo Silva (2013)
The castor bean is a plant resistant to the adverse conditions of soil and climate, with the main product the ricinoleic oil, with potential for the production of renewable fuel. This speciesby its characteristics, falls among those considered suitable for fertilization with sewage sludge. However, while the sewage sludge is rich in nutrients and organic matter, it may contain heavy metals in concentrations that can affect the health of plants and animals. The aim of this study was to evaluate the risk of contamination of soil and castor plant with heavy metals with the application of sewage sludge, compared with chemical fertilization. The experiment consisted of 4 doses of sewage sludge applied to the soil (0; 2,63; 5,25 e 10,5 Mg ha-1) plus an additional treatment (chemical fertilizer), distributed in a randomized block design with six repetitions. The application of sewage sludge did not promote elevation of the levels of Cd, Cr, Ba, Se, Hg, Zn, Cu, Pb and Ni in the soil and in the plant in harmful levels to the environment. Moreover, the levels of these metals in the soil and in the plant fertilized with sewage sludge were similar to soil fertilized with chemical fertilizers. With the application of increasing doses of sewage sludge, the levels in the soil of metals Zn and Cu increased linearly. On the other hand, the leaves of castor plant, increasing the doses of sewage sludge did not influence the concentrations of Zn and Cu, although it has increased the content of Zn and the exportation of this metal with the harvest.